PENGARUH STRUKTUR MODAL, BELANJA MODAL, DAN KEPUTUSAN INVESTASI TERHADAP PROFITABILITAS PERUSAHAAN - Melsi Guswindi; Eka Rosalina; Eliyanora Eliyanora (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the effect of capital structure, capital expenditure, and investment decisions on company profitability. The research adopts a quantitative approach. The population consists of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Data analysis was conducted using Stata version 14. The analytical methods used include descriptive statistics, panel data regression analysis, model selection tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results show that capital structure has a significant effect on company profitability. Meanwhile, capital expenditure and investment decisions do not have a significant effect on profitability. However, simultaneously, capital structure, capital expenditure, and investment decisions collectively influence profitability.